2013
DOI: 10.12659/msmbr.883912
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical study and phase I clinical safety evaluation of recombinant Mycobacterium tuberculosis ESAT6 protein

Abstract: BackgroundTo investigate the ability of rESAT6 to identify different mycobacteria-sensitized guinea pigs and its safety in preclinical and phase I clinical study.Material/MethodsGuinea pigs were sensitized with different Mycobacteria. After sensitization, all animals were intradermally injected with rESAT6 and either PPD or PPD-B. At 24 h after the injection, the erythema of the injection sites were measured using a double-blind method. For the preclinical safety study, different doses of rESAT6 and BSA were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…In animal studies, intradermal tests with ESAT6 and a combination of ESAT6 with CFP10 protein had shown safety and sensitivity to inducing specific skin test responses [17,18]. Several large and ongoing follow-up studies in humans have also shown specificity and sensitivity, proof of safety, feasibility, and dosage tolerability of a recombinant dimeric version of ESAT6 (rdESAT6) [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies, intradermal tests with ESAT6 and a combination of ESAT6 with CFP10 protein had shown safety and sensitivity to inducing specific skin test responses [17,18]. Several large and ongoing follow-up studies in humans have also shown specificity and sensitivity, proof of safety, feasibility, and dosage tolerability of a recombinant dimeric version of ESAT6 (rdESAT6) [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Para esse procedimento, além das técnicas de lise mecânica como a desrupção ultrassôni-ca e método físico como o choque térmico (congelamento/ descongelamento), é necessário lançar mão do processo de lise química utilizando agentes caotrópicos como a uréia e o hidrocloreto de guanidina que rompem as interações não covalentes, aumentam a solubilidade das substâncias apolares e desfazem as interações hidrofóbicas desnaturando as proteínas. No entanto, se levarmos em consideração que a imunotoxicidade é a questão mais importante à cerca dos reagentes utilizados para o diagnóstico intradérmico que depende de uma resposta imunológica (Du et al 2013), esses agentes desnaturantes precisam ser totalmente removidos das amostras proteicas por apresentarem toxicidade celular. Contudo, o processo de diálise de 72 h empregado nesse estudo parece não ter sido suficiente para completa remoção desses reagentes das amostras proteicas.…”
Section: Discussionunclassified
“…They showed that in treated TB patients, the responses to recombinant dimmer ESAT-6 were optimal at 0.1 μg (in 0.1 mL) [ 23 ]. Our phase I study showed that intradermal injection of 0.1 mL of 1 (15 cases), 5 (18 cases), and 10 μg/mL (10 cases) recombinant ESAT-6 protein is safe for human volunteers, and only a few local adverse events such as pain, itching, and blister occurred following ESAT-6 injection [ 17 ]. In the present study, administration of 0.1 mL of all doses, ranging from 2 to 10 μg/mL of ESAT-6, was well-tolerated by healthy volunteers and patients with pulmonary TB.…”
Section: Discussionmentioning
confidence: 99%
“…However, its promise for the use in the skin test has never been evaluated in humans. In a phase I study, we performed a preliminary assessment of the safety of a recombinant M. tuberculosis ESAT-6 protein in Chinese volunteers [ 17 ]. Then, we performed a phase II trial to examine the diagnostic performance and safety of the recombinant M. tuberculosis ESAT-6 protein used as a skin test for the diagnosis of pulmonary TB.…”
Section: Introductionmentioning
confidence: 99%